How economic freedom affect the ease of doing business? Cross-country quantile regression mixture approach - Kilic Depren, Serpil; Depren, Ozer (YILDIZ TECHNICAL UNIV, 2021)
The significance of the Economic Freedom Index (EFI) dimensions as influencing factors of the Ease of Doing Business Index (EDB) has been increasing in recent years. The main purpose of this study is to examine the nexus between the dimensions of EFI and EDB using 160 countries between 2017 and 2019. Considering that the impact of EFI dimensions on the different levels of EDB may differ, the Quantile Regression Mixture Model approach is applied in this study. Thus, the impact of the dimensions of EFI on EDB will be analyzed in different quantiles. The results show that there are five different clusters where the impact of the dimensions of EFI on EDB are differentiated. The major finding of this study is that Property Rights, Trade Freedom, and Business Freedom are the most important factor affecting EDB. As a result of the study, it is shown that different action plans should be created for each cluster to increase EDB.
Keywords: Economic freedom; Quantile regression mixture models; Doing business; FOREIGN DIRECT-INVESTMENT; ENTREPRENEURSHIP; CORRUPTION; GROWTH; Engineering